Interacting mast cells and eosinophils acquire an enhanced activation state in vitro. Issue 2 (4th December 2012) - Elishmereni, M.; Bachelet, I.; Ben‐Efraim, A. H. N.; Mankuta, D.; Levi‐Schaffer, F.
Abstract Background Mast cells (MCs) and eosinophils (Eos), the key effector cells in allergy, are abundantly co‐localized particularly in the late and chronic stages of allergic inflammation. Recent evidence has outlined a specialized 'allergic effector unit' in which MCs and Eos communicate via both soluble mediators and physical contact. However, the functional impact of this bi‐directional crosstalk on the cells' effector activities has not yet been revealed. We aimed to investigate whether MC/eosinophil interactions can influence the immediate and late activation phenotypes of these cells. Methods Human and murine MCs and Eos were co‐cultured under various conditions for 1–2 h or 1–3 days, and in selected experiments cell–cell contact was blocked. Cell migration and mediator release were examined, and flow cytometry was applied to stain intracellular signaling molecules and surface receptors. Results Eosinophils enhanced basal MCs mediator release and co‐stimulated IgE‐activated MCs through physical contact involving CD48–2B4 interactions. Reciprocally, resting and IgE‐stimulated MCs led to eosinophil migration and activation through a paracrine‐dependent mechanism. Increased phosphorylation of activation‐associated signaling molecules, and enhanced release of tumor necrosis factor α, was observed in long‐term co‐cultures. Eosinophils also showed enhanced expression of intercellular adhesion molecule 1, which depended on direct contact with MCs. Conclusions Our findings reveal a new role for MC/eosinophil interplay in augmenting short‐ and long‐term activation in both cells, in a combined physical/paracrine manner. This enhanced functional activity may thus critically contribute to the perpetuation of the inflammatory response in allergic conditions.